Neighbourhood effects in cross-Atlantic perspective: A longitudinal analysis of impacts on intergenerational mobility in the USA and Germany. (February 2019) - Howell, Junia
Research in the USA provides evidence that neighbourhood conditions affect intergenerational mobility. However, what remains unclear is the extent to which the US context is unique in producing this influence. To examine this question, the present study directly compares neighbourhood effects on intergenerational mobility in the USA versus those in Germany – a country whose housing market and social welfare policies differ significantly from those in the USA. Results provide a blueprint for conducting cross-national neighbourhood effects studies and illuminate how the nature and severity of neighbourhood effects are nationally specific. These findings underscore the importance of considering how broader political contexts shape neighbourhood effects on intergenerational mobility – a consideration that has implications for proposed policy interventions.